PENGGUNAAN FITUR E-ZAKAT SEBAGAI MEDIA PENYALURAN HASIL ZAKAT FITRAH KEPADA MUSTAHIQ - Muhamad Awiet Wiedanto Prasetyo awiet (LPPM Universitas Al Asyariah Mandar, 2020)
In order to facilitate the process of collecting, managing and distributing zakat, the amil zakat fitrah Baitul Yamin Mosque distributes the amil body’s tasks to be at the hamlet and community level because they have a distance from each other and pass through village or regency road access to the village center. With these problems, there are supporting facilities such as 4G base provider network access that facilities smoother communication but still experiences problems when calculating the final result that results in an error of acceptance by mustahiq. The research method is that the team leader conducts an interview with the village apparatus to find out the problems that exist in the community which can later be solved by using information technology. Then the team leader conducts an interview again to the chairman of the committee of the Baitul Yamin Mosque Amil Zakat Board to get information on the constraints during the zakat fitrah activities each year and to formulate the existing problems immediately resolved. The E-Zakat feature that has been produced is very beneficial for the amil zakat body of Kedunggede Village is assisting the data collection and distribution of zakat fitrah. With a simple display that helps the zakat bodies understand how to operate the zakat application that has been made from the login to enter the data of who gets zakat and the percentage of zakat obtained by each mustahiq.